Workplace Health: Engaging Business Leaders to Combat Obesity. Issue 2 (December 2013) - Lankford, Tina; Lang, Jason; Bowden, Brian; Baun, William
<x xml:space="preserve">Abstract</x> This article explores how employers can be part of the solution to obesity by offering workplace wellness programs and facilitating opportunities for physical activity, access to healthier foods and beverages, and incentives for disease management and prevention to help prevent weight gain among their employees.